Space jam : a new legacy [videorecording (DVD)] - Lee, Malcolm D., 1970-; James, LeBron; James, LeBron; Cheadle, Don; Davis, Khris (SDS, 2021)
LeBron James and his son are trapped by a rogue AI in a Warner Bros.-themed digital universe where their only chance to free themselves is to form a basketball team out of Looney Tunes characters and compete against the AI's own team.